2003
DOI: 10.1590/s0085-56262003000400004
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Cinara spp. (Hemiptera, Aphididae) by Cycloneda sanguinea (Linnaeus, 1763) and Hippodamia convergens Guérin-Méneville, 1842 (Coleoptera, Coccinellidae)

Abstract: ABSTRACT. Adults and larvae of coccinellids were observed feeding on populations of the giant conifer aphids Cinara spp. on Pinus spp., in Southern Brazil. The objective of this research is to evaluate the consumption capacity of Cycloneda sanguinea (Linnaeus, 1763) and Hippodamia convergens Guérin-Méneville, 1842 (Coleoptera, Coccinellidae) on these aphid species, in order to obtain information for biological control programs. Ten larvae of each predator species were fed with aphids of small size (nymphs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
3
2
2
Order By: Relevance
“…Taking into account the number of viable eggs, H. convergens and C. sanguinea had similar results; and for the number of eggs per oviposition, H. convergens superseded C. sanguinea (Table 2). Cardoso & Lázzari (2003) observed that adults of C. sanguinea had longevity of 167.1 days when kept at 20 o C and, despite the difference in temperature, these results are close to the values of 147.0 (females) and 162.8 days (males) found in the present study.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Taking into account the number of viable eggs, H. convergens and C. sanguinea had similar results; and for the number of eggs per oviposition, H. convergens superseded C. sanguinea (Table 2). Cardoso & Lázzari (2003) observed that adults of C. sanguinea had longevity of 167.1 days when kept at 20 o C and, despite the difference in temperature, these results are close to the values of 147.0 (females) and 162.8 days (males) found in the present study.…”
Section: Resultssupporting
confidence: 91%
“…Larval stage duration of H. convergens (11.02 days) was approximately the same as the results by Cardoso & Lázzari (2003) at 25 o C (10.9 days), and shorter than that reported by Kato et al (1999) (13.7 days). The duration of 4.48 days for the pupal period was similar to the 4.5 days obtained by Kato et al (1999), and shorter compared to the 6.3 days determined by Cardoso & Lázzari (2003), who added to this time the pre-pupal stage. Hippodamia convergens sex ratio (50%) was lower than the 60% proportion found by Kato et al (1999).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations